(untitled) (International Journal of Engineering and Computer Science, 2017)
Traffic congestion has become a major problem in this technical era. There are various reasons for this traffic congestion. One of these is the rapid growth of the population. As a result of this, the number of cars is increasing annually. The increase in the number of trucks and commercial vehicles also causes traffic congestion. This causes problems for the ambulance to reach the hospital on the right time. As the result of the rapid growth of technology and engineering field the life of the mankind has got automated. This automation is the process of making the electronic device to communicate between themselves to serve the purpose of the human. The one of the major field that concentrate on the automation is Internet of Things creatively called as IoT. This project is based on the IoT and cloud to save the human life at critical situation. This project is to establish the communication between the traffic signals and the ambulance so that the traffic signal can respond to the arrival of the ambulance and respond according to that. When the traffic signals are changes its states according to the position of the ambulance it can able to make a free way for the ambulance. Thus this project will act as a life saver.